Brain Biopsies: Does technique matters? - Jha, Rajiv; Shrestha, Rajendra; Rajbhandari, Binod; Aryal, Sameer; Bhattarai, Sushil Mohan; Gautam, Sindhu; Paudel, Kumar; Khadka, Namrata; Jalan, Pankaj (Nepal Journal of Neuroscience, 2025)
Introduction: This study aims to analyze the diagnostic yield of various brain biopsy techniques performed at the National Neurosurgical Referral Center (NNRC), National Academy of Medical Sciences (NAMS), Bir Hospital, Kathmandu, Nepal, to identify brain pathologies such as infections, tumors, inflammations, demyelinating diseases, and other conditions. Materials and Methods: This retrospective study reviewed 188 cases of brain biopsies conducted at NNRC over a specified period. Biopsies were performed using diverse techniques, including open free- hand biopsy, open biopsy, CT-guided biopsy, frame-based biopsy, frameless biopsy and endoscopic biopsy. Patient demographics, clinical presentations, imaging findings, biopsy techniques, and histopathological results were analyzed. Diagnostic yield was calculated as the percentage of cases where a definitive diagnosis was obtained. Results: Of the 188 cases, a diagnostic yield of 93% was achieved, highlighting the effectiveness of these biopsy techniques in diagnosing a wide range of brain pathologies. Tumors represented the most common pathology diagnosed, followed by infections, inflammatory conditions, and demyelinating diseases. The choice of biopsy technique depended on the lesion’s location, size, and clinical scenario. Advanced techniques like CT-guided and Frame-guided biopsies demonstrated high accuracy in sampling deep-seated or eloquent brain areas. Conclusion: Brain biopsy remains an invaluable tool for diagnosing diverse intracranial pathologies with a high diagnostic yield. The integration of advanced imaging and guided techniques has significantly enhanced the safety and accuracy of the procedure. This study emphasizes the need for tailored biopsy approaches based on individual clinical and radiological profiles to maximize diagnostic outcomes. Further research and technological advancements are recommended to improve diagnostic efficacy and reduce complications.